MAPPING OF MANGROVES CHANGE AREA AND THE DENSITY OF MANGROVE IN ANAK SETATAH VILLAGE SUB-DISTRIC OF RANGSANG BARAT DISTRICT OF KEPULAUAN MERANTI RIAU PROVINCE - Halida Sisda Harahap; Elizal Elizal; Efriyeldi Efriyeldi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was conducted in February 2019 in Anak Setatah village, Sub-distric of West Rangsang, District of Kepulauan Meranti, Riau Province and was aimed to find out the change of area and the density of mangrove this time. The research was conducted by survey method. The quantitative method was used on the change of mangrove forest area observation. The result of image data processing showed that mangroves area in Anak Setatah Village had decrease of area in 2006-2011 about 3.77 ha and there was an increase of area in 2011-2016 about 116.88 ha. The density of mangrove in Anak Setatah Village has the tight and medium density type. According to Mangrove Quality Standards, the density are still in Good category.  Key words : Mangrove, Change of Area, Density, Anak Setatah